Study on the Advantages and Novel Strategies to Teaching Indonesian in Elementary Schools through the Incorporation of Deep Learning and Total Physical Response integrated Content-Language based Learning through the Whole Language Method - Agustin, Nadya Dewinda; Yarmi, Gusti (Unika Santu Paulus Ruteng, 2025)
This research aims to examine the trends, innovations, and challenges in acquiring Indonesian language skills in elementary education. The main findings of this research emphasize critical areas such as new innovations in Indonesian language learning based on Deep Learning with the Total Physical Response integrated Content-Languagebased Learning through the Whole Language Method approach (TPR-CLIL-WLM). This research underscores the importance of collaboration between theory, principles of character values, and technology in enhancing the acquisition of Indonesian language skills. This research significantly contributes to building a foundation for future research and education, especially in the integration of locally-based innovations with deep learning methodologies in the global context of the Indonesian language. Deep Learning prioritizes student engagement through thinking, feeling, acting, and reflecting, resulting in active student participation with enjoyable and meaningful awareness. Whole language integrates students' social-functional-linguistic experiences with contextual elements in PPBI. Total Physical Response and Content-Language based Learning uphold the development of students' sociocultural constructivist perspectives. The integration of Teaching and Learning Indonesian Language (TLIL) based on Deep Learning through the TPR-CLIL-WLM approach focuses on the learning process rather than the learning outcomes, which tend to filter students with certain competencies, thus greatly valuing each student's abilities, needs, and processes. Thus, this integration is highly recommended. In addition, this integration also stimulates students to enhance the 6Cs skills as 21st-century essential skills.